Third Five-Year Plan of Bangalore District Government of Mysore - Planning Commission (Planning Commission, 1965)
The Third Plan envisages a magnitude of effort which is much greater than that of the previous Plan. The crucial test, however, lies in its implementation. For a full realisation of its benefits, the Plan has to be implemented with the highest possible efficiency at all levels,—especially so at the levels of the District, Block and Village. For it is in these areas of activity that a wide range of plan programmes is translated into its concrete physical shape.
Government of Mysore, Planning, Housing and Social Welfare Department